2019
DOI: 10.33096/substantivejustice.v2i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Regional Autonomy in Realizing Good Governance

Abstract: Good Governance in regional autonomy is a phenomenon whose principle is talking about government or good government in terms of realizing good governance through the context of public services. The purpose of regional autonomy is solely to provide satisfaction to the community and prosperity of society in a government area. The purpose of this study is to determine the development of current regional autonomy in realizing Good Governance as intended. The research method used in the preparation of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 5 publications
0
26
0
7
Order By: Relevance
“…From several years that have been running, it can be seen that from 2016 to 2020 the Mahakam Ulu government as a new autonomous region has focused its development on the basic needs of the community, such as improving service quality, acceleration of economic development, infrastructure development, and development of regional areas. It shows that the new autonomous region is a real effort to improve people's welfare, accelerate development, and improve access to quality public services (Moonti 2019, Sulistiowati 2014). The United Nations Development Programme (2011) also revealed that the presence of inclusive communities aims to form communities that can present access to all components of society to secure equal opportunities for all things in their social interactions.…”
Section: Inclusive Community Development In Mahakam Ulu Districtmentioning
confidence: 99%
See 4 more Smart Citations
“…From several years that have been running, it can be seen that from 2016 to 2020 the Mahakam Ulu government as a new autonomous region has focused its development on the basic needs of the community, such as improving service quality, acceleration of economic development, infrastructure development, and development of regional areas. It shows that the new autonomous region is a real effort to improve people's welfare, accelerate development, and improve access to quality public services (Moonti 2019, Sulistiowati 2014). The United Nations Development Programme (2011) also revealed that the presence of inclusive communities aims to form communities that can present access to all components of society to secure equal opportunities for all things in their social interactions.…”
Section: Inclusive Community Development In Mahakam Ulu Districtmentioning
confidence: 99%
“…The seriousness and alignments of local governments Mahakam Ulu have seen in the vision of the RPJMD-I, which, if we look at the formulation and implementation of its programs, has adjusted to the fulfillment of the four pillars of SDGs (Fukuda-Parr 2016, Kementerian Perencanaan Pembangunan Nasional 2020). The new regional autonomy can improve community welfare, accelerate development, and improve access to quality public services, ultimately creating inclusive communities in Mahakam Ulu (Moonti 2019, Sulistiowati 2014.…”
Section: The Realization Of Development Planning In Mahakam Ulumentioning
confidence: 99%
See 3 more Smart Citations